2013
DOI: 10.3758/s13428-012-0300-3
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Thurstonian models for ranking data using JAGS

Abstract: A Thurstonian model for ranking data assumes that observed rankings are consistent with those of a set of underlying continuous variables. This model is appealing since it renders ranking data amenable to familiar models for continuous response variables-namely, linear regression models. To date, however, the use of Thurstonian models for ranking data has been very rare in practice. One reason for this may be that inferences based on these models require specialized technical methods. These methods have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…While calculating the exact posterior distribution is generally intractable, Markov Chain Monte Carlo (MCMC) algorithms can provide a robust approximation of the posterior (J. K. Kruschke, 2015). It has been shown that MCMC algorithms can be used to fit BTMs (Yao and Böckenholt, 1999;Yu, 2000;and Johnson and Kuhn, 2013), and can be implemented in probabilistic programming frameworks such as JAGS (Johnson and Kuhn, 2013). MCMC algorithms work by indirectly taking a representative sample from the joint posterior distribution.…”
Section: Bayesian Estimation and Markov Chain Monte Carlomentioning
confidence: 99%
See 3 more Smart Citations
“…While calculating the exact posterior distribution is generally intractable, Markov Chain Monte Carlo (MCMC) algorithms can provide a robust approximation of the posterior (J. K. Kruschke, 2015). It has been shown that MCMC algorithms can be used to fit BTMs (Yao and Böckenholt, 1999;Yu, 2000;and Johnson and Kuhn, 2013), and can be implemented in probabilistic programming frameworks such as JAGS (Johnson and Kuhn, 2013). MCMC algorithms work by indirectly taking a representative sample from the joint posterior distribution.…”
Section: Bayesian Estimation and Markov Chain Monte Carlomentioning
confidence: 99%
“…MCMC algorithms have previously been applied to Thurstonian models using a "rank censoring constraint" which obviates the need to analytically evaluate the likelihood function. The rank censoring constraint essentially ensures that the Markov Chain has zero probability of transitioning to locations in parameter space where does not have the same rank as (see Johnson and Kuhn, 2013, for an overview). Popular MCMC algorithms, such as the Metropolis algorithm (Hastings, 1970;Metropolis, Rosenbluth, Rosenbluth, Teller, & Teller, 1953) work by first proposing a transition in parameter space, and then accepting the transition according to a probabilistic acceptance criterion…”
Section: Bayesian Estimation and Markov Chain Monte Carlomentioning
confidence: 99%
See 2 more Smart Citations
“…8], [91]. Other possible software are JAGS [86, p. 214], [50,78,108]; SAS (SAS Institute, Cary NC) [86,Ch. 8], [128]; etc.…”
Section: Random Coefficients and Bayesian Inferencementioning
confidence: 99%